Evaluating Capacity-Building through Literature: A Review of Studies on the Training and Development of Cooperative Development Officers in the Philippines - Toledo, Ralph Rendell; De Jesus, Emerlita; Estrada, Darriela Lane; Sotoza, Josue Jr.; Garces, Clarence (JPAIR Multidisciplinary Research, 2025)
In the Philippines, the professionalization of Cooperative Development Officers (CDOs) has been institutionalized through the implementation of Republic Act No. 11535, which was signed into law on April 9, 2021, and Memorandum Circular No. 2023-12, issued by the Cooperative Development Authority (CDA). The purpose of this study is to evaluate the available research on CDO training, with a particular emphasis on adult learning principles, training evaluation systems, and the connection between demographic profiles and training outcomes. The analysis highlights important frameworks, including Kirkpatrick's Four-Level Evaluation Model, Knowles' Adult Learning Theory, and the CIPP (Context, Input, Process, Product) Model, by using a thorough literature review process. These models are crucial resources for assessing the efficacy of training, directing ongoing development, and guaranteeing that the results apply to regional situations. This study highlights essential themes that inform the design, delivery, and evaluation of CDO capacity-building programs by employing a systematic approach to analyze scholarly works and official issuances. Other sources of information that are reviewed include government publications. The findings underscore the importance of being sensitive to demographics, implementing tailored instruction, and evaluating students based on their achievements. In conclusion, the article offers recommendations that can guide future program enhancements, aligning with the aims of inclusive competency-based development.
Keywords: Cooperative Development Authority; Cooperative Development Officers; adult learning; training evaluation; demographic profiles; CDA Training program; competency-based development